Unprecedented use of NHC gold (I) complexes as catalysts for the selective oxidation of ethane to acetic acid - Ribeiro, Ana Paula da Costa; Matias, Inês A. S.; Zargaran, Poorya; Hashmi, A. Stephen K.; Martins, Luísa M. D. R. S. (Materials, 2021)
The highly efficient eco-friendly synthesis of acetic acid (40% yield) directly from ethane is achieved by the unprecedented use of N-heterocyclic carbene (NHC) and N-heterocyclic oxo-carbene (NHOC) gold(I) catalysts in mild conditions. This is a selective and promising protocol to generate directly acetic acid from ethane, in comparison with the two most used methods: (i) the three-step, capital- and energy-intensive process based on the high-temperature conversion of methane to acetic acid; (ii) the current industrial methanol carbonylation processes, based in iridium and expensive rhodium catalysts. Green metrics determinations highlight the environmental advantages of the new ethane oxidation procedure. Comparison with previous reported published catalysts is performed to highlight the features of this remarkable protocol.
Gesehen am 13.09.2021